IMPROVING STUDENTS’ SPEAKING SKILL THROUGH TOPIC SELECTION METHOD AT THE THIRD SEMESTER OF ENGLISH EDUCATION STUDY PROGRAM UMI (Karya Ilmiah Mahasiswa (KIMA), 2024)
AbstractThe focus of this research was to find the effectiveness and the student’s responses to the topic selection method. The researcher applied a pre-experimental design by using a one-group pre-test and post-test design. This research was conducted in class C2 at the third semester of the English Education study program Universitas Muslim Indonesia which involved 8 students as the research sample. The researcher used an oral test consisting of pre-test, treatment, and post-test and then conducted a questionnaire to measure students' responses. The researcher conducted pre-test, treatment, post-test, and the researcher found the percentage of improvement increase was 144,4% and the student’s responses were 76% (Very High), Based on the data above showed that the majority of respondents had a positive attitude in using Topic Selection method in the third-semester English education study program at Universitas Muslim Indonesia. The conclusion of this research the Topic selection method was effective in improving students' speaking skill.